Sound production and sonic apparatus in deep-living cusk-eels (Genypterus chilensis and Genypterus maculatus). (November 2018) - Parmentier, E.; Bahri, M.A.; Plenevaux, A.; Fine, M.L.; Estrada, J.M.
Abstract: Cusk-eels (Ophidiidae) are known sound producers, but many species live in deep water where sounds are difficult to record. For these species sonic ability has been inferred from inner anatomy. Genypterus (subfamily Ophidiinae) are demersal fishes inhabiting the continental shelf and slope at depths between 50 and 800 m. Males and females G. maculatus have been maintained together in a tank and 9 unsexed specimens of G. chilensis in a second tank, providing a valuable opportunity to record the sounds of living species usually found at great depths. Genypterus chilensis and G. maculatus respectively produced one and two sound types mainly between 7 and 10 pm. Sound 1 in Genypterus maculatus consists of trains of pulses that vary in amplitude and pulse period; call 2 sounded like a growl that results from the rapid emission of pulses that define sound 1. Genypterus chilensis produced a growl having an unusual feature since the first peak of the second pulse has always greater amplitude than all other peaks. These sounds are probably related to courtship behavior since floating eggs are found after night calls. The anatomical structures of the sound-producing organ in both species present an important panel of highly derived characters including three pairs of sonic muscles, a neural arch that pivots on the first vertebral body and a thick swimbladder with unusual features. Sonic structures are similar between species and between sexes. Therefore both biological sexes are capable of sound production although precedent from shallow ophidiids and sonic fishes in general suggests that males are more likely to produce courtship calls. This study reports two main types of information. It demonstrates that two deep-living species are capable of sound production, which is a pioneer step in the acoustic study of deep-sea fauna. Recorded sounds should also help to locate fish in open sea. As these species are currently used to diversify the aquaculture industry in Chile, deeper studies on their acoustic behavior should also help to target spawning period and to identify mature specimens. Graphical abstract: Highlights: Cusk-eels (Genypterus chilensis and G. maculatus) are capable of sound production. Sounds are probably related to courtship behavior; both sexes are able to make calls. Sounds could be used to improve rearing of Genypterus species in aquaculture. Deep-living species are able to use acoustic communication.